Tratamientos de dientes permanentes inmaduros con formación radicular incompleta - Huaira Dayanna, Tixilema Yanchaliquin (2021)
ABSTRACT The treatment of immature teeth with incomplete root formation involves a series of techniques to preserve or replace the affected structures of the dentin-pulp complex in teeth that have not finished their root formation process and apical closure. These treatments are vital pulp therapy, apexification, regenerative endodontics are alternatives to rehabilitate the tooth that has not finished its root development. This literature review was carried out to analyze the different treatments for immature teeth with incomplete root formation. A literature search was carried out in scientific articles in dental health, compiled through databases such as Pubmed, Springer link, Elsevier, Scielo, Google scholar through exclusion and inclusion criteria, filters, average citation count (ACC), impact factor indicator of the journal located in the Scimago Journal Ranking (SJR), after applying the selection criteria a total of 100 articles were obtained to carry out the systematic review. It was concluded that the most frequent treatments in immature teeth reported in the different studies were: pulpotomy, apexification, and regenerative endodontics. Pulpotomy was shown to be an effective alternative for treating vital teeth, while apexification and regenerative endodontics are valid options for treating teeth with necrosis if the cases are correctly diagnosed. It was determined that the success and failure rate of the techniques were 90%-100% for pulpotomy, 74%-100% for apexification, and 96.5% for regenerative endodontics. Keywords: treatment of immature teeth, vital pulp therapy, apexification, regenerative endodontics. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258